LITERACY ANALYSIS OF TADULAKO UNIVERSITY PGSD STUDENTS - Rizal Rizal; Sucitra Dewi (Jurnal Dikdas, 2020)
This study aims to determine the literacy ability of students at the Tadulako University Primary School Teacher Education. The sample in this study were class B class 2018 students of Tadulako University Elementary School Teacher Education totaling 40 students, 6 men and 34 women, the data collection techniques used were questionnaires, interviews, and documentation. Furthermore, the collected data is processed and analyzed using qualitative data and quantitative data analysis as a support. Qualitative data is data that is descriptive in nature, information and information in the form of numbers. And quantitative data in the form of numbers in the questionnaire. From the results of this study indicate that of the 40 student respondents that can be seen from the percentage of answers is always at 12%, while 16% answered frequently, 36% answered occasionally, 25% answered rarely, and 11% answered never. So based on these data it can be concluded from several alternative indicators that are available. Students prefer to answer sometimes and at least answer never. This means that the literacy ability of Tadulako University Primary School Teacher Education students is still quite sufficient